Design, synthesis, and in vitro evaluation of N-(3-(3-alkyl-1H-pyrazol-5-yl) phenyl)-aryl amide for selective RAF inhibition. Issue 4 (15th February 2019) - Jung, Hoyong; Kim, Jinwoong; Im, Daseul; Moon, Hyungwoo; Hah, Jung-Mi
Graphical abstract: Abstract: Notorious oncogenic BRAF V600E plays a significant role in the signal transduction of the MAPK pathway, which is involved in tumor growth, especially in melanoma. Much effort has been made to suppress BRAF V600E through small molecules like vemurafenib and dabrafenib, but the MAPK pathway remains active through paradoxical activation, where CRAF transmits the signal of the MAPK pathway either alone or along with BRAF V600E. Therefore, we designed and synthesized a new series of N -(3-(3-alkyl-1 H -pyrazol-5-yl) phenyl)-aryl amide/urea analogues that showed potent inhibitory activities against BRAF V600E and CRAF. Compound7c exhibited particularly superior selectivity toward BRAF V600E and CRAF over 30 other protein kinases, implying that this chemotype could be investigated as a BRAF paradox breaker. © 2019 Elsevier Ltd. All rights reserved.